Heterogeneous effects of economic policy uncertainty and financial development on global renewable energy consumption - Muhammad Tariq Majeed; Anwar Shah; Hafsah Batool (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The objective of this study is to analyze the role of economic policy uncertainty (EPU) and financial development in shaping renewable energy consumption employing panel data of 130 economies from 1990 to 2020. The empirical analysis is based on pooled ordinary least squares, fixed effects, random effects, and system generalized method of moments estimation techniques. The empirical outcomes suggest that EPU is positively connected with global renewable energy consumption (REC). This effect, however, is not consistent across developed and developing economies. In developed countries a rise in EPU is positively linked with REC while in middle- and low-income economies the EPU is negatively associated with REC. Similarly, the effects of financial development on REC vary across income groups. It exerts a favorable effect on REC in developed countries. On the contrary, it has a negative influence on REC in developing countries. These findings suggest that rich economies are taking benefit of REC drivers while the developing world is not exploiting the favorable role of these drivers. Finally, the study also predicts the statistically significant role of economic prosperity, trade, and inflation in explaining the REC. The study offers useful policy implications.
Keywords: 330; clean energy consumption; economic policy uncertainty; trade; growth; financial development; inflation; developing economies